2020
DOI: 10.1111/epi.16422
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐dependent modulation of cortical and thalamic sensory responses during spike‐and‐wave discharges

Abstract: Objective The neuronal underpinnings of impaired consciousness during absence seizures remain largely unknown. Spike‐and‐wave (SW) activity associated with absences imposes two extremely different states in cortical neurons, which transition from suprathreshold synaptic depolarizations during spike phases to membrane hyperpolarization and electrical silence during wave phases. To investigate whether this rhythmic alternation of neuronal states affects the processing of sensory information during seizures, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 60 publications
(129 reference statements)
1
5
0
Order By: Relevance
“…In control conditions, the firing probability of thalamo-cortical cells in response to sensory stimuli was 0.49 ± 0.37 (n = 9 neurons). The corresponding mean number of sensory-evoked APs per stimulation was 1.30 ± 0.40 (n = 9 neurons) and the latency of the first evoked AP, relative to air-puff onset, was 17.1 ± 4.7 ms (n = 9 neurons), a value similar to that previously reported for the same cell population (Brecht & Sakmann, 2002;Williams et al 2020) and compatible with the latency of cortical neurons dPSPs (13-20 ms). Sensory responsiveness of thalamo-cortical neurons was found to be largely reduced during the electro-cerebral inactivity.…”
Section: Silencing Of Thalamo-cortical Neurons and Dampening Of Thalasupporting
confidence: 88%
See 2 more Smart Citations
“…In control conditions, the firing probability of thalamo-cortical cells in response to sensory stimuli was 0.49 ± 0.37 (n = 9 neurons). The corresponding mean number of sensory-evoked APs per stimulation was 1.30 ± 0.40 (n = 9 neurons) and the latency of the first evoked AP, relative to air-puff onset, was 17.1 ± 4.7 ms (n = 9 neurons), a value similar to that previously reported for the same cell population (Brecht & Sakmann, 2002;Williams et al 2020) and compatible with the latency of cortical neurons dPSPs (13-20 ms). Sensory responsiveness of thalamo-cortical neurons was found to be largely reduced during the electro-cerebral inactivity.…”
Section: Silencing Of Thalamo-cortical Neurons and Dampening Of Thalasupporting
confidence: 88%
“…A similar injection protocol, using greater current intensities (2–5 nA) granted a reliable labelling of the juxta‐cellularly recorded cells (Williams et al . 2020). Rats were then rapidly killed with euthasol and transcardially perfused with a fixative solution containing 0.3% glutaraldehyde‐4% paraformaldehyde in phosphate‐buffered saline (0.1 m , pH 7.4) (VWR Chemicals, Fontenay‐sous‐Bois, France).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for the higher frequency of spike-wave oscillations in rodents is not yet well understood, but experimental and theoretical work has proposed that it may involve species differences in the prevalence of GABAergic receptor subtypes affecting the duration of the oscillatory cycle (Destexhe, 1999;Destexhe et al, 1999;Sanchez-Vives et al, 2021). Consistent findings in cats and rats show that these abnormal oscillations dynamically alter the intrinsic excitability of cortical neurons, impeding their ability to integrate and process sensory information efficiently (Neckelmann et al, 2000;Williams et al, 2016Williams et al, , 2020. It has therefore been suggested that such instability of sensory representations during seizures may contribute to impairing the cortical functions necessary for normal conscious experience (Williams et al, 2020).…”
Section: Absence Epilepsymentioning
confidence: 99%
“…77,165 Moreover, regions in the brain during absence seizures show decreases in CBF and metabolism. 166 It is unclear if the anaesthetic reductions in CBF and metabolic activity cause unconsciousness or if they are a result of alterations in network interactions. 33 Patients recovering from a vegetative state who regained consciousness, for example, continued to show substantially decreased global cerebral metabolism.…”
Section: Cerebral Blood Flow and Metabolic Activitymentioning
confidence: 99%